Protein kinase G inhibition preserves photoreceptor viability and function in a new mouse model for autosomal dominant retinitis pigmentosa - Yu Zhu; Lucia Peiroten; Pranav Nanda Kumar; Catherine Hottin; Kangwei Jiao; Wadood Haq; François Paquet-Durand (Cell Death and Disease)
Abstract Retinitis Pigmentosa (RP) is the most common inherited retinal degeneration, characterized by an initial loss of rod photoreceptor cells. Photoreceptor cell death has been associated with high levels of cyclic guanosine-3′, 5′- monophosphate (cGMP) in animal models of autosomal recessive RP (ARRP) and autosomal dominant RP (ADRP). cGMP analogues inhibiting protein kinase G (PKG) have been found to prevent rod degeneration in ARRP disease models, but their effects on ADRP are unknown. Here, we used the recently generated rhodopsin-mutant Rho I255d/+ ADRP mouse model to study cGMP-signaling and the effects of cGMP analogues targeting PKG. cGMP accumulation was investigated by retinal immunostaining in wild-type (WT), Rho I255d/+, and Rho I255d/I255d mice. The therapeutic efficacy of the cGMP analogues CN03 and CN238 was evaluated on organotypic retinal explant cultures derived from WT and Rho I255d/+ mice. Readouts included the TUNEL assay and immunostaining for cone arrestin-3. Downstream effectors of cell death were visualized using calpain, poly-ADP-ribose polymerase (PARP), and histone deacetylase (HDAC) in situ assays, as well as caspase-3 immunostaining. Photoreceptor function was assessed using micro-electroretinogram (µERG) recordings. When compared with WT, Rho I255d photoreceptors displayed cGMP accumulation in outer segments. In the Rho I255d/+ ADRP model, CN03 and CN238 significantly reduced the number of dying photoreceptors. However, the relatively small number of photoreceptors exhibiting caspase-3 activity was not changed by the treatment. Remarkably, CN238 effectively provided long-lasting neuroprotection of cone photoreceptors and preserved retinal light responsiveness of Rho I255d/+ retina. Overall, this study suggests caspase-independent but cGMP-dependent cell death as a dominant degenerative mechanism in the Rho I255d/+ ADRP mouse model. PKG inhibition demonstrated robust neuroprotection of both rod and cone photoreceptors, while the marked preservation of retinal function, especially with the compound CN238, highlighted cGMP analogues for the treatment of ADRP.